2018
DOI: 10.2136/vzj2018.02.0028
|View full text |Cite
|
Sign up to set email alerts
|

Methane Transport during a Controlled Release in the Vadose Zone

Abstract: Shallow, small-rate releases of ethanol-blended fuels from underground storage tanks (USTs) may be quite common and result in subsurface CH 4 generation. However, vadose zone transport of CH 4 generated from these fuel releases is poorly understood, despite the potential to promote vapor intrusion or create explosion hazards. In this study, we simulated shallow CH 4 generation with a controlled subsurface CH 4 release from July 2014 to February 2015 to characterize subsurface CH 4 migration and surface emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The high concentrations of VOCs recorded after the third test could have been mobilized by the nitrogen gas injected into the borehole. Studies has also shown that the migration of CH 4 and CO 2 induces the migration of VOCs from contaminated sites (Katy et al, 2009;Felice et al, 2018) and therefore may be another reason.…”
Section: Resultsmentioning
confidence: 99%
“…The high concentrations of VOCs recorded after the third test could have been mobilized by the nitrogen gas injected into the borehole. Studies has also shown that the migration of CH 4 and CO 2 induces the migration of VOCs from contaminated sites (Katy et al, 2009;Felice et al, 2018) and therefore may be another reason.…”
Section: Resultsmentioning
confidence: 99%
“…Field moisture, efflux, and soil gas for the entire duration of the CH 4 injection period have been previously discussed in detail (Felice et al, 2018), but measurements from the final period of CH 4 injection are briefly summarized here to provide context for the microbial data that follow.…”
Section: Resultsmentioning
confidence: 99%
“…Field characterization and a detailed description of the CH 4 release and measurement of efflux, soil gas, and soil moisture were described in detail by Felice et al (2018). Briefly, a monitoring network consisting of soil gas sampling points installed at 0.5, 1.0, and 1.5 m (with additional points at 0.25 and 1.75 m in the center of the network) below ground surface (bgs); polyvinyl chloride collars for gas efflux measurement; and soil temperature sensors was established at the Putah Creek Riparian Reserve in Davis, CA (Fig.…”
Section: Field Site Methane Injection and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Methane, an important component of greenhouse gas, is often generated at municipal landfills and petroleum-hydrocarbon-contaminated sites. Methane transport in vadose zone soils has the potential to promote vapor intrusion or create explosion hazards if its generation in the subsurface environment is unnoticed or poorly managed [1]. Adequately assessing the migration of a methane gas plume in the subsurface is important for effective strategy design and management regarding methane releases.…”
Section: Introductionmentioning
confidence: 99%